Application of ecological momentary assessment in stress-related diseases - Yoshiuchi, Kazuhiro (BioMed Central, 2008)
Many physical diseases have been reported to be associated with psychosocial factors. In these diseases, assessment relies mainly on subjective symptoms in natural settings. Therefore, it is important to assess symptoms and/or relationships between psychosocial factors and symptoms in natural settings. Symptoms are usually assessed by self-report when patients visit their doctors. However, self-report by recall has an intrinsic problem; "recall bias". Recently, ecological momentary assessment (EMA) has been proposed as a reliable method to assess and record events and subjective symptoms as well as physiological and behavioral variables in natural settings. Although EMA is a useful method to assess stress-related diseases, it has not been fully acknowledged, especially by clinicians. Therefore, the present brief review introduces the application and future direction of EMA for the assessment and intervention for stress-related diseases.